REKONTRUKSI ILMU PERSPEKTIF MAQASHID AL SYARIAH (FILSAFAT ILMU SEBAGAI UPAYA MEMBANGUN ETIKA KEILMUAN) - Dania Fadhilatul Hikmah (LP2M IAIN Sultan Amai Gorontalo, 2026)
on maqashid al-sharia as a response to moral crises and ethical problems in the development of modern science. This research uses a library research method with a qualitative-philosophical approach. Data were obtained through a critical review of relevant classical and contemporary literature, then analyzed using content analysis combined with philosophical reflection on the ontology, epistemology, and axiology aspects of science. The results of the study show that the integration of maqashid al-sharia into the philosophy of science produces a scientific paradigm that is full of values, not ethically neutral, and interest-oriented. Ontologically, science is understood as a reality that must be on the side of the protection of religion, soul, intellect, descent, and property. Epistemologically, the process of acquiring knowledge is required to be not only methodologically valid, but also morally responsible. Axiologically, the use of knowledge is directed to prevent damage and realize social good. The conclusion of the study emphasizes that the reconstruction of science based on maqashid al-sharia is a strategic foundation in building integrative, humanist, and sustainable scientific ethics, while placing scientists as moral guardians in the development of science